Innovation Tourism Information System to Support Post-Covid-19 Health Protocols and Halal Tour in The Special Area of Yogyakarta - Trio Yonathan Tejakusuma; Arya Wirabhuana; Izra Berakon (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2023)
Yogyakarta is one of the regions in Indonesia whose tourism sector has been affected by the Covid-19 pandemic. All tourism actors, especially onAlmost none of the MSME and informal sectors can escape the economic downturn due to the Covid-19 pandemic. They lost their income because tourist visits dropped by almost 100 percent. This is very worrying because it is known that Yogyakarta is one of the cities which is a tourist destination in Indonesia. The reopening of tourism objects after Covid-19 has become a momentum and turning point in promoting and developing the potential for halal tourism in DIY. The establishment of DIY as one of the National Priority Halal Destinations by the Ministry of Tourism in 2018 prompted the DIY government to encourage tourism actors such as restaurants and hotels to take part in halal certification from the Indonesian Ulema Council to ensure and increase consumer confidence in the halal tourism services provided.In general, the problems that are the object of discussion and are resolved within the scope of this research include identifying indicators that must be considered in developing tourism in DIY so that it complies with the Covid-19 Health protocol and the concept of Halal Tourism. In addition, it will also determine the characteristics of the Tourism Information System needed by Stakeholders in order to be able to support the implementation of the Covid-19 Health Protocol in the